1998
DOI: 10.1346/ccmn.1998.0460110
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of Fundamental Illite Particle Thicknesses by X-Ray Diffraction Using PVP-10 Intercalation

Abstract: Abstract~The thicknesses of fundamental illite particles that compose mixed-layer illite-smectite (I-S) crystals can be measured by X-ray diffraction (XRD) peak broadening techniques (Bertaut-WarrenAverbach [BWA] method and integral peak-width method) if the effects of swelling and XRD background noise are eliminated from XRD patterns of the clays. Swelling is eliminated by intercalating Na-saturated I-S with polyvinylpyrrolidone having a molecular weight of 10,000 (PVP-10). Background is minimized by using po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(34 citation statements)
references
References 20 publications
(33 reference statements)
0
34
0
Order By: Relevance
“…Accurate results may be obtained by removing the effect of swelling interlayers either by large scale expansion (Eberl et al, 1998a) or by heating (Drits et al, 1998). The KI properties for anchizone values (Table 2) may explain the good results of the Bertaut-Warren-Averbach method without using special treatment.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Accurate results may be obtained by removing the effect of swelling interlayers either by large scale expansion (Eberl et al, 1998a) or by heating (Drits et al, 1998). The KI properties for anchizone values (Table 2) may explain the good results of the Bertaut-Warren-Averbach method without using special treatment.…”
Section: Discussionmentioning
confidence: 94%
“…The Bertaut-Warren-Averbach method is not relevant for interstratified clay minerals without special treatment (Warren and Averbach, 1950;Drits et al, 1998;Eberl et al, 1998a), as shown by Lanson and Kiabler (1994). Accurate results may be obtained by removing the effect of swelling interlayers either by large scale expansion (Eberl et al, 1998a) or by heating (Drits et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The illite mineral association, contained in the light yellow-green friable rock on cave walls, is a typical product of hydrothermal alteration of rocks. The thickness of coherent diffracting domains without expanding interlayers indicates temperature of hydrothermal fluids close to 300°C (see Eberl et al, 1998;Šucha, 2000). The origin of quartz crystals and illite mineral association has been connected with the hydrothermal origin of adjacent large epithermal vein system (before the formation of the cave).…”
Section: Hydrothermal Speleogenesis In Basement Carbonates Of the Strmentioning
confidence: 99%
“…Free expansion of smectites in water is almost unlimited. Completely dispersed smectite particles consist of single unit cells with no c-axis direction repeat distance (Eberl et al, 1998). Interlayer expansion of air-dried (32% relative humidity) samples of Na-smectite and Ca-smectite is illustrated in Figure 1 with characteristic basal spacings after McEwan & Wilson (1984).…”
mentioning
confidence: 98%